2018
DOI: 10.1111/jace.15720
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the thermoelectric performance of Bi2O2Se by isovalent doping

Abstract: N‐type Bi2O2Se has a bright prospect for mid‐temperature thermoelectric applications on account of the intrinsically low thermal conductivity. However, the low carrier concentration of Bi2O2Se (~1015 cm−3) severely limits its thermoelectric performance. Herein, the boosting of the carrier concentration to ~1019 cm−3 can be realized in our La‐doped Bi2O2Se ceramic samples, which could be ascribed to the formation of isoelectronic traps and the narrowing of band gap, and contribute to a marked increase in the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 51 publications
2
31
1
Order By: Relevance
“…As reported, there are two types of crystal structure with the same I4/mmm space group for tetragonal Bi 2 O 2 Se, whose structural discrepancy lies in the O atom position as was shown in Figure 4e,f, which makes it difficult to be distinguished by using XRD. [26] As shown in Figure S4a,b, Supporting Information, the experimental data fits well with the simulated model both in R space and k space, indicating the robust structural model based on structure type II. In contrary, the other fit model based on structure type I was rejected with a considerable large R-factor.…”
Section: Synchrotron X-ray Absorption Spectroscopy Studysupporting
confidence: 65%
“…As reported, there are two types of crystal structure with the same I4/mmm space group for tetragonal Bi 2 O 2 Se, whose structural discrepancy lies in the O atom position as was shown in Figure 4e,f, which makes it difficult to be distinguished by using XRD. [26] As shown in Figure S4a,b, Supporting Information, the experimental data fits well with the simulated model both in R space and k space, indicating the robust structural model based on structure type II. In contrary, the other fit model based on structure type I was rejected with a considerable large R-factor.…”
Section: Synchrotron X-ray Absorption Spectroscopy Studysupporting
confidence: 65%
“…First, Bi 2 O 2 Se was suggested to be a good thermoelectric material. [2][3][4][5][6][7] In 2010, Ruleova et al reported the thermoelectric properties of Bi 2 O 2 Se and they found that Bi 2 O 2 Se is an n-type semiconductor with a very low thermal conductivity and a relatively high gure of merit ZT about 0.2 at 800 K. 2 Several theoretical works were also conducted to explore its thermoelectric properties. [8][9][10][11] Second, Bi 2 O 2 Se has an ultrahigh electron mobility.…”
Section: Introductionmentioning
confidence: 99%
“…For the low electronegativity dopant atoms, the ability to attract holes is stronger, which facilitates the formation of a hole bound state, triggering the excitation of electrons and increasing the concentration of electrons. In contrast, the high electronegativity dopant atoms will form an electron bound state which increases the concentration of holes [32,33]. shown in Figure 3(b), the carrier concentration of pristine Bi 2 O 2 Se (shown in brackets) is only 1:55 × 10 15 cm -3 indicating the characteristics of insulators.…”
Section: Point Defectsmentioning
confidence: 96%
“…After La doping, the carrier concentration is boosted up to~10 19 cm -3 corresponding to the characteristic of a degenerate semiconductor, which contributes to the significant enhancement in electrical conductivity from 0.03 Scm -1 to 182 Scm -1 . Profited from the boosted electrical conductivity, the ZT value of Bi 2−x La x O 2 Se is significantly enhanced, which shows the feasibility of inducing isoelectronic trap to optimize carrier concentration and ZT value [33].…”
Section: Point Defectsmentioning
confidence: 98%
See 1 more Smart Citation